The Unwanteds - McMann, Lisa (Aladdin, 2012)
In a society that purges thirteen-year-olds who are creative, identical twins Aaron and Alex are separated, one to attend University while the other, supposedly Eliminated, finds himself in a wondrous place where youths hone their abilities and learn magic.